Nutritional health aspects and functional properties of nut yogurt: Future perspectives - Jiangxia Zhai; Yongliang Zhuang; Liping Sun; Ying Gu; Xuejing Fan (Food Chemistry: X)
The increase in lactose intolerance, the rise of veganism, the pursuit of healthy lifestyles, environmental awareness and concern for animal welfare have led to an increase in consumer demand for plant-based yogurts. The high nutritional value of nuts makes them an ideal ingredient for the production of plant-based yogurts. The main challenge for such products is to achieve a similar taste to traditional yogurt while improving shelf life. In recent years, extensive research has been conducted on this topic. The nutritional and health properties of yogurts made from different types of nuts, traditional and innovative processing technologies, and the effects of fermentation on the nutritional value, sensory characteristics, and texture of the yogurts are described. This review provides a comprehensive overview of the nutritional and manufacturing process of nut yogurts and offers possible directions for development and innovation of health food products.